HUBUNGAN KEBIJAKAN FISKAL DENGAN DISTRIBUSI PENDAPATAN MASYARAKAT DI PROPINSI DAERAH ISTIMEWA YOGYAKARTA - Aan M Yunianto (Jurnal Bisnis dan Ekonomi, 2007)
Many countries pursuing high economic growth less pay attention to economic distribution. The uneven revenue distribution is a serious problem of every nation. A country which merely pursues economic growth without concerning revenue even distribution will result in revenue partiality. One of ways to reduce revenue partiality is by using fiscal policy through progressive tax system. In Yogyakarta Special Province, the problem of  revenue distribution partiality is interesting to be investigated due to PDRB increase from year to year turned out that it does not followed by the decline of the number of poor people in Yogyakarta Special Province, but rather followed by increasingly the number of poor people. The fact of PDRB increase from year to year and the increase of those number of poor people can be used as one of indicators there exists inequitability of development outcomes. This research aimed at understanding until how much does the level of center tax progressiveness in Yogyakarta Special Province and studying center tax influence to the social revenue distribution in Yogyakarta Special Province. In order to find out the level of center tax progressiveness, it has been used Kakwani Progressiveness Index, whereas in order to find out the correlation between  center tax and  the revenue distribution, it was performed by comparing between Gini Index before tax and Gini Index after tax. To strengthen finding results, it then, was conducted statistic test so that the best results were obtained. Out of calculation results, it turned out obtained that all types of center tax are progressive in nature, but the level of greatest progressiveness is on type of Property Tax (PBB), while type of Value Addition Tax (PPN) has the level of lowest progressiveness. In addition, a theory that stated that a tax able to improve social revenue distribution within this research does not proved, due to within it Gini Index result after tax is rather bigger than Gini Index before tax. It means the level of social revenue distribution partiality is grower and grower. Key words:  partiality, revenue distribution, fiscal policy, tax, progressive,  Gini Index